Etiology of vitreous hemorrhage in a tertiary eye care center in Nepal - Sharma, R; Joshi, SN; Shrestha, JK (Nepalese Journal of Ophthalmology, 2010)
Introduction: Vitreous hemorrhage is one of the most common differential diagnoses of sudden painless decrease in vision. Objective: To find out the etiology of vitreous hemorrhage in cases of vitreous hemorrhage at a tertiary eye centre in Nepal. Materials and methods: This was a hospital-based cross-sectional study done over a period of one-and-a-half years. One hundred and one subjects with vitreous hemorrhage were evaluated in detail to establish the etiology. Statistics: The mean value and standard deviation were calculated. The data were analyzed using microsoft excel and SPSS 11.5 program. Results: A total of 122 eyes of 101 patients were evaluated. The mean age was 41.90 (± 21.50) years with a range of 2 months to 84 years. Male were 73 %. Bilateral involvement was found in 20.8 %. Proliferative diabetic retinopathy, retinal vasculitis, branch retinal vein occlusion, rhegmatogenous retinal detachment together with ocular trauma constituted the etilogoy of vitreous hemorrhage in more than 75 % of patients. Conclusion: Proliferative diabetic retinopathy, retinal vasculitis and branch retinal vein occlusion are the most common causes of vitreous hemorrhage in adults whereas in children trauma is the commonest cause. Keywords: vasculitis; vitreous hemorrhage; diabetic retinopathy; Eales disease DOI: 10.3126/nepjoph.v2i2.3718 Nep J Oph 2010;2(2) 121-126